2000
DOI: 10.1128/jb.182.10.2702-2708.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas Quinolone Signal Regulates rhl Quorum Sensing in Pseudomonas aeruginosa

Abstract: The opportunistic pathogen Pseudomonas aeruginosa uses intercellular signals to control the density-dependent expression of many virulence factors. The las and rhl quorum-sensing systems function, respectively, through the autoinducers N-(3-oxododecanoyl)-L-homoserine lactone and N-butyryl-L-homoserine lactone (C 4 -HSL), which are known to positively regulate the transcription of the elastase-encoding gene, lasB. Recently, we reported that a second type of intercellular signal is involved in lasB induction. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
311
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(328 citation statements)
references
References 25 publications
9
311
2
6
Order By: Relevance
“…Although the LasI/R QS system plays a dominant role in the complex QS hierarchy in P. aeruginosa (34), three QS systems, namely, LasI/R, RhlI/R, and PQS, all participate in a complex signaling network to regulate lasB gene expression (29). Recently, it was reported that production of PQS is completely abrogated during anaerobic growth of P. aeruginosa (43,51).…”
Section: Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the LasI/R QS system plays a dominant role in the complex QS hierarchy in P. aeruginosa (34), three QS systems, namely, LasI/R, RhlI/R, and PQS, all participate in a complex signaling network to regulate lasB gene expression (29). Recently, it was reported that production of PQS is completely abrogated during anaerobic growth of P. aeruginosa (43,51).…”
Section: Cellmentioning
confidence: 99%
“…P. aeruginosa QS is also regulated by another system, which involves potentiation of transcriptional activation by MvfR (also known as PqsR) upon binding of a Pseudomonas quinolone signal (PQS) (55). The PQS/MvfR complex actively participates in the intertwined P. aeruginosa QS network, and accumulating evidence now suggests that PQS-mediated QS is absolutely required for the uninterrupted production of elastase (29,36).…”
mentioning
confidence: 99%
“…However, a lasR mutant is still able to produce PQS, although at a later stage in growth (Diggle et al, 2003). The PQS signal, if supplemented exogenously, is capable of restoring production of elastase encoded by lasB, which is normally LasR dependent (McKnight et al, 2000;Gallagher et al, 2002;Pesci et al, 1999). Due to their central role in expression of multiple virulence traits in P. aeruginosa and the fact that they function by means of low-molecular-mass extracellular signal molecules, the QS systems are clearly potential antibacterial drug targets.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…LasR has been shown to regulate PQS production, and RhlR is required for PQS activity (Pesci et al, 1999). PQS has been shown to induce expression of lasB, the gene encoding LasB elastase, and rhlI (McKnight et al, 2000;Pesci et al, 1999). PQS has also been implicated in the regulation of the secondary metabolites pyocyanin and hydrogen cyanide (Gallagher et al, 2002).…”
Section: Introductionmentioning
confidence: 99%